KH. Husain Muhammad's View on Kafa'ah in Marriage to Form a Happy Family - Muhamad Adlan; Moh. Yustafad (Legitima : Jurnal Hukum Keluarga Islam, 2021)
In marriage, kafaah can be understood as compatibility and balance between the bride-to-be and her husband so that each individual does not experience difficulties in carrying out marriage. In society, there is a term Bibit (offspring) Bebet (economic status) Weight (the height and low quality of a person) is a measure in choosing a life partner. The concept of kafaah in this study is juxtaposed with the thoughts of KH. Husain Muhammad as a kyai figure who explores the interpretation of verses about gender and often fights for gender rights. This research includes qualitative research and research data obtained by interview method and additional data from books and scientific articles related to kafaah. The results of this study explain that kafaah according to KH. Husain Muhammad is a match or suitability between a couple. And the suitability referred to by him ideally there are four aspects, then the priority is ad-din. Ad-din in this context is interpreted as a measure of compatibility in unuversal morality or in the sense of morals, not something outwardly idealistic.